Design of multiple-stage hydraulic cylinder for structural safety and sealing analysis - Qi Haonan; Rivaldo Mersis Brilianto; Minsu Choi; Chul Kim (Scientific Reports)
Abstract Multi-stage telescopic hydraulic cylinders are used in cranes, trucks, and factories. Due to the large working distance of horizontal multi-stage hydraulic cylinders, large deflections appear with several structural safety problems, such as leakages. Recently, several researchers have used the finite element analysis to analyse the structural safety of multi-stage hydraulic cylinders at their maximum working location; however, the relationship between the large deflection and the sealing problem has not been discussed much. In this study, focused on reducing the deflection effect of the five-stage cylinder sealing problem, using the developed singularity deflection equation to describe the deflection values under different diameter ratios for the five-stage hydraulic cylinder and comparing these with FEA results, noting a maximum error of 14%. The rod eye mounting direction with its install methods was designed to minimize deflection, and the structural large deflection was performed using an ANSYS workbench. Additionally, sealing performance tests were carried out for three commonly used hydraulic seals (O-ring, Rectangular-ring, U-seal). The results confirmed that under large deflection effects, different areas on the same seal exhibit varying contact pressures. Ageing tests under cyclic pressure and temperature fluctuations, verifying that the U-seal, compared to other seals, enhances the structural safety of the five-stage hydraulic cylinder and reduces wear. Furthermore, compared with the O-ring and rectangular seal, the U-lip seal was suggested for better structural safety and reduced wear in the five-stage hydraulic cylinder. Following the optimisation of the U-ring seal, the average contact pressure was reduced by 8.02% compared to the original O-ring design.